Audiologic Outcomes After Oval and Round Window Reinforcement Surgery. Issue 7 (August 2021) - Conway, Robert M.; Tu, Nathan C.; Pinther, Steven; Shareef, Zaid; Hong, Robert S.; Zappia, John J.; Babu, Seilesh C.
Abstract : Introduction: Oval window (OW) and round window (RW) reinforcement surgery has been used for symptomatic treatment of multiple clinical entities, most commonly perilymphatic fistula and superior semicircular canal dehiscence. Owing to the theoretical acoustically negative effect of stiffening the windows, there has been concern of an unfavorable effect on audiologic outcomes due to the procedure. The purpose of this study is to specifically evaluate audiologic outcomes after OW and RW reinforcement. Methods: A retrospective review of patients undergoing transcanal OW or RW reinforcement was completed. Patients were evaluated both as a total group and as two groups separated into "third window" and "two-window" groups based on their specific diagnosis. Primary outcomes included changes in individual pure-tone thresholds, pure-tone average (PTA), air-bone gap, speech reception threshold (SRT), and word recognition scores (WRS) between the preoperative and postoperative groups. Results: Seventy-one patients were included in the study. The combined cohort demonstrated a significant postoperative 2.75 dB increase in the air conduction hearing level at 4000 Hz ( p < 0.05). This was almost entirely accounted for by a 2.18 dB increase in the air-bone gap at this frequency ( p < 0.05). There were no significant changes in PTA, SRT, or WRS between in the combined group or in the subgroup analysis. Conclusion: OW and RW tissue reinforcement resulted in a statistically significant but likely clinically insignificant decrease in hearing at the 4000 Hz frequency. There was no worsening of PTA, WRS, or SRT.